A multi-dimensional decision framework for modular value transfer activity. Issue 5 (4th April 2021) - Doran, Desmond; Morgan, Royston; Morgan, Stephanie; Giannakis, Mihalis; Subramanian, Nachiappan
Abstract: This paper explores the key dimensions and value-adding elements of a supply chain delivering cockpit modules to an automotive assembly operation in the United Kingdom. The findings demonstrate that supplying on a modular basis is influenced by the initial design decisions of the Original Equipment Manufacturer (OEM), the capabilities of the Module supplier and the ability to offer greater levels of customisation in a high-volume environment. The research articulates the findings through the concept of the 'Dimensions of Modularity' which seeks to demonstrate the key decision areas in a modular context and extend the concept of 'Value Transfer Activity' within a modular context. Our research provides insights into the specific dynamics of a module supply chain from OEM through to Modular supplier and a supplier of sub-modules. From this research, those involved in developing modular solutions can determine the multi-dimensional issues that need to be addressed to ensure that the supply chain is effectively connected and value transfer implications are accommodated and maximised. By adopting a single supply chain approach to exploring the impact of modular practices this paper provides valuable observations into an area of supply chain and operations management that is becoming increasingly relevant to both academic and practitioner communities.